A re-investigation of the thio effect at the hammerhead cleavage site. - Scott, E C (1999)
The effect of introducing a phosphorothioate at the hammerhead cleavage site was investigated using a kinetically well-characterized hammerhead. In buffers containing Mg ion, the RP-phosphorothioate isomer cleaved 2000- to 80 000-fold slower than the SPisomer or the unmodified RNA substrate. Addition of low concentrations of several thiophilic metal ions, especially Cd2+, to these reactions is sufficient to fully restore the cleavage rate of the RPsubstrate without affecting cleavage rate of the all-oxygen or SPsubstrate. Thus, a model proposing coordination of a divalent metal ion to the pro-R oxygen at the hammerhead cleavage site appears justified.